Hemoglobin status in pregnant women for diagnosis of anemia, assessment of severity and its socio-demographic determinants in rural area of Kanpur district, Uttar Pradesh, India - Prajapati, Beenu; Gautam, Praveen Kumar; Arya, Manju Lata (International Journal of Research in Medical Sciences, 2018)
Background: Anaemia is one of the most common nutritional deficiency disorders affecting the pregnant women in the developing countries. In India anaemia in pregnancy is a major health issue with adverse maternal and foetal outcome. Nutritional anaemia in pregnant women continues to be a cause of concern despite the fact that this problem is largely preventable and easily treatable. Objectives was to determine the prevalence and severity of anaemia in the pregnant women. Methods: Around 350 pregnant women in different trimesters of pregnancy were enrolled coming for the 1st time in outpatient department of Obstetrics and Gynaecology, in Rama Medical College Hospital and Research Centre, Kanpur from Janurary 2016 to December 2016. Information regarding age, age at marriage, age at 1st pregnancy, parity, Interval between previous and index pregnancy, no of abortions, educational status, dietary habits, Type of family, Socioeconomic status was collected in pre-designed structured schedule after taking written consent from pregnant women attending out-patient department. Haemoglobin estimation was done by auto analyser and anaemia was graded according to WHO criterion. Statistical analysis was done by percentages and proportions. Results: A high prevalence of anaemia, (87.71%) was observed in pregnant women. The current study shows (24.7%) cases of mild anaemia, (54.5%) cases of moderate anaemia, and (7.9%) of severe anaemia. Conclusions: A very high prevalence of anaemia in pregnancy needs awareness about late marriage, birth spacing, one or two child norm, antenatal care, green leafy vegetable in diet, mandatory regular supply of iron folic acid (IFA) tablets to adolescent and pregnant women along with correction of other nutritional deficiencies.